(untitled) - Needleman, Raphael (New York, 1990)
Contents: The fundamentals; technology overview; LANs in practice; Extending your reach.
Keywords: Local area networks (Computer networks),Mạng cục bộ (mạng máy tính); Microcomputer,Vi máy tính